"You can never understand a culture until you experience it": How an experiential learning course prepared students for practice with Latino communities through learning for advocacy. Issue 3 (27th May 2018) - Revens, Keri E.; Reynolds, Andrew D.; Suclupe, Roger F.; Rifkin, Cameron; Pierce, Taylor
ABSTRACT: This study used grounded theory to analyze focus group data of students participating in an experiential learning course developed in partnership with a local Latino-serving community agency. A central phenomenon, Learning for Advocacy, emerged from the data, describing a process through which students' personal encounters led to the development of awareness and perspective taking, thereby encouraging students to develop an advocacy orientation for practice with Latino clients and communities. Study findings highlight (a) how experiential courses support students' development of an advocacy orientation and (b) how social work programs in newly emerging Latino communities might approach the development of an experiential learning course to prepare students to serve these communities.